ISLAM & PERUBATAN ALTERNATIF - Mifedwil Jandra Janan, author; Aminuddin Hehsan, author; Abdul Basit Samat @ Darawi, contributor; Ahmad Marzuki Mohamad, 1963-, contributor; Aminuddin Hehsan, contributor; Aminuddin Ruskam, 1962-, contributor; Ajmain @ Jimaain Safar, contributor; Azmi Shah Suratman, 1959-, contributor; Mohd. Nasir Ripin, contributor; Mohd. Ismail Mustari, 1967-, contributor; Nurazmallail Marni, contributor; Nur Syazwani Mohd. Hanafiah, 1989-, contributor; et al. (Johor Bahru, Johor : Penerbit UTM Press, 2016)
Includes bibliographical references and index :p.97